2000
DOI: 10.1084/jem.191.1.9
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Factor of Activated T Cells (Nfat) Transcription Factor Nfatp (Nfatc2) Is a Repressor of Chondrogenesis

Abstract: Nuclear factor of activated T cells (NFAT) transcription factors regulate gene expression in lymphocytes and control cardiac valve formation. Here, we report that NFATp regulates chondrogenesis in the adult animal. In mice lacking NFATp, resident cells in the extraarticular connective tissues spontaneously differentiate to cartilage. These cartilage cells progressively differentiate and the tissue undergoes endochondral ossification, recapitulating the development of endochondral bone. Proliferation of already… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
150
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(166 citation statements)
references
References 79 publications
13
150
0
3
Order By: Relevance
“…In the adult heart, calcineurin signaling has a central role in cardiac hypertrophy (Bueno et al, 2002b). In addition to the heart, calcineurin signal transduction is active during development and adult adaptive responses of skeletal muscle, neurons, and the immune system, and there is emerging evidence for the importance of this signaling pathway in cartilage, skin, and smooth muscle (Baksh and Burakoff, 2000;Olson and Williams, 2000;Ranger et al, 2000;Graef et al, 2001bGraef et al, , 2003Crabtree and Olson, 2002). These initial studies have all been performed using mammalian systems and tissue culture.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult heart, calcineurin signaling has a central role in cardiac hypertrophy (Bueno et al, 2002b). In addition to the heart, calcineurin signal transduction is active during development and adult adaptive responses of skeletal muscle, neurons, and the immune system, and there is emerging evidence for the importance of this signaling pathway in cartilage, skin, and smooth muscle (Baksh and Burakoff, 2000;Olson and Williams, 2000;Ranger et al, 2000;Graef et al, 2001bGraef et al, , 2003Crabtree and Olson, 2002). These initial studies have all been performed using mammalian systems and tissue culture.…”
Section: Discussionmentioning
confidence: 99%
“…These bone marrow stem cells are pluripotent and capable of differentiating into several lineages such as chondrocytes, myocytes, and adipocytes in addition to osteoblasts (3). Interestingly, Cn/NFAT signaling has been shown to play a critical role in the lineage decision of stem cells to differentiate into chondrocytes, myocytes, and adipocytes (34,36,37). Indeed, the global deletion of NFATc2 in mice has been shown to increase the expression of chondrocytic-specific genes and chondrogenesis, suggesting that NFATc2 is a negative regulator of chondrocyte growth and differentiation (37).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Cn/NFAT signaling has been shown to play a critical role in the lineage decision of stem cells to differentiate into chondrocytes, myocytes, and adipocytes (34,36,37). Indeed, the global deletion of NFATc2 in mice has been shown to increase the expression of chondrocytic-specific genes and chondrogenesis, suggesting that NFATc2 is a negative regulator of chondrocyte growth and differentiation (37). Global NFATc2/c4 double knock-out mice exhibit defects in fat accumulation and reduced adiposity, suggesting that NFAT signaling is positive regulator of adipogenesis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the role of NFAT1 in other systems, it has been shown that lack of NFAT1 induces neoplastic transformation of cartilage cells and increased susceptibility to chemically-induced sarcoma formation in mouse models. 46,59 Also, constitutively active NFAT1 (CA-NFAT1) was able to antagonize H-RasV12 oncogene-induced transformation of NIH 3T3 fibroblasts. 46 Collectively, these data suggest a tumor suppressor role for NFAT1 in different cell types.…”
Section: Discussionmentioning
confidence: 99%